Protein and polyphenol structure transformation persuade “colloid-suspension” phase conversion in green tea beverages - Xinxin Wang; Lin Wang; Yunqing Liu; Yani Pan; Xinyu Feng; Wenzhi Ling; Xiangru Wang; Sitong Zhong; Yili Shen; Ranran Zhao; Yuefei Wang; Ping Chen; et al. (Food Chemistry, 2026)

Hyperelastic NaLuS2:Ho/Yb-TPU composite fiber for dual-modal optical sensing of temperature and strain in smart motion monitoring - Xinxin Jing; Zhimin Yu; Yue Li; Edwin Yue Bun Pun; Hai Lin (Chemical Engineering Journal, 2026)

Ce, N, S co-doped carbon dots with synergistically enhanced peroxidase-like activity for glucose biosensing and ROS-mediated cytotoxic effect - Xinxin Xu; Junjie Li; Yutong Wu; Jialu Wang; Yuru Lin; Ningning Wang; Zhaohui Li (Analytica Chimica Acta, 2026)

Targeting the NLRP3/Caspase-1 pyroptotic pathway exacerbates insulin resistance upon exposure to nanoplastics with different surface chemistries - Xinxin Yao; Yu Cao; Sue Lin; Shihua Chen; Feiqin Xie; Wenhui Xu; Yize Wu; Qiufang Wu; Renyi Peng; Xiaohua Gong (Journal of Hazardous Materials, 2026)

Dopamine-functionalized gel for rapid iodine and triiodide capture through adsorption-conversion pathway in aqueous media - Xinxin Li; Lin Jiang; Feng Lin; Zikang He; Rongzhi Tang; Yu Tan (Chemical Engineering Journal, 2026)

Janus composite membranes for suppressing thermal wetting in membrane distillation of flue gas desulfurization wastewater - Xinxin Lin; Qiaoling Ye; Binbin Li; Huiyi Cai; Caiyi Fan; Zhongsen Yan (Journal of Water Process Engineering, 2026)

Simultaneous multi-biomarker detection: streptavidin-biotin mediated high-quality quantum dot immunosensor with signal amplification - Huanhuan Xing; Ruixue Zhang; Ning Li; Xiaoquan Li; Zoi G. Lada; Theocharis C. Stamatatos; Xinxin Chen; Huaibin Shen; Dangdang Xu; Xiaojing Xing; Ruili Wu; Lin Song Li (Analytica Chimica Acta, 2026)

Transcriptomic changes of starch and sugar conversion during storage of potato tubers treated with citronella essential oil - Xinxin Guan; Lei Zhu; Wenqiang Guan; Qianqian Zhang; Xuan Wang; Xingxing He; Qiong Lin (Postharvest Biology and Technology, 2026)

Synthesizing high-performance zeolite X from coal gangue for flue gas CO2 capture - Jiahao Liu; Xianghao Li; Xinru Zhang; Nien-Chu Lai; Zeyi Jiang; Lin Lin; Xinxin Zhang (Journal of Environmental Chemical Engineering, 2026)

Two-step single B cell technology for high-affinity rabbit monoclonal antibodies: development of a highly sensitive immunoassay for monensin in raw milk - Jingjie Huang; Ao Lin; XinXin Ma; Yanzhe Qing; Yani Gu; Xiaole Pan; Jiancheng Li (Food Chemistry, 2026)

Waste activated sludge derived biopolymer amelioration for desert sand: Impact on moisture retention, vegetation growth and microbial community - Sudan Lin; Yujiao Zhang; Xinxin Zong; Chao Xu; Lin Li; Haifeng Zhang; Dong-Hoon Kim; Boyan Xu; Ratnaweera Harsha; Xueqing Shi (Journal of Cleaner Production, 2026)

Robust, thermal insulated cellulose porous films for durable and efficient radiative cooling - Xinxin Chen; Mengxiang Dang; Longfei Sun; Yusong Xu; Yu Liu; Lin Liu; Guocheng Zhu; Juming Yao (Carbohydrate Polymers, 2026)

Flame-retardant and electromagnetic-interference-shielding silver nanowire/silicon dioxide/aramid nanofiber/sodium alginate lightweight porous composite for wearable sensors - Xinxin Cai; Hui Liu; Wen Li; Jiwen Hu; Xiaobin Li; Shudong Lin (Carbohydrate Polymers, 2026)

Impact of the Surface Roughness of Artificial Oyster Reefs on the Biofouling and Flow Characteristics Based on 3D Scanning Method - Yenan Mao; Shimeng Sun; Mingchen Lin; Hui Liang; Yanli Tang; Xinxin Wang (Journal of Marine Science and Engineering, 2026)
The complex surface architecture of natural oyster reefs is widely considered to promote biological attachment, yet the underlying mechanisms and the relevance to the design of artificial reefs are not fully understood. Here, we combined field experiments, 3D surface characterization, and numerical modelling to quantify how reef-like roughness regulates biofouling development and near-wall flow around artificial substrates. Surface morphological characteristics of natural oyster reefs were first obtained by 3D scanning and used to fabricate concrete panels with simulated rough textures, while traditional smooth concrete panels served as controls. The two types of panels were simultaneously deployed in the target sea area for a hanging-panel experiment. Samples were collected after 3, 6, 9, and 12 months to track changes in biofouling communities. At each sampling time, the panel surfaces were quantified by canopy roughness (RC), surface heterogeneity (σ), and fractal dimension (D), and these metrics were integrated into numerical simulations combined to resolve the flow field, turbulence kinetic, and near-wall shear stress around the colonized panels. The research results show that, after 12-month immersion, the mean thickness of the biofouling layer on rough and control panels reached 6.39 mm and 5.91 mm, respectively. Rough panels exhibited consistently higher RC and σ than controls, and these two parameters are strongly linearly correlated (R2=0.891). Numerical simulations reveal that increased RC enlarges the oyster settlement shear-stress window (OSSW), indicating more favorable hydrodynamic conditions for oyster settlement and growth on rough panels. Nevertheless, the hydrodynamic differences between the initial rough panels and control panels gradually diminish over time, suggesting that biological growth can progressively naturalize initially smooth substrates. These findings advance the mechanistic understanding of how small-scale roughness and biofouling co-evolve to shape oyster habitat quality and provide a quantitative basis for the eco-engineering design of artificial oyster reefs.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Policy-driven water quality trends in Qinhuangdao coastal waters, China (2003–2024): Nutrient controls and climate vulnerabilities via high-accuracy hue angle - Lin Wang; Xiang Wang; Xinxin Wang; Qinghui Meng; Zhijie Wang (Regional Studies in Marine Science, 2026)

Quinoline-driven response and functional remodeling of the anaerobic digestion system - Tingting Cui; Chunhui Zhang; Siqi Liang; Zhao Zhang; Liwei Wang; Xinxin Zhang; Leyi Chen; Zepeng Wang; Zhiwei Lin; Yanxin Li; Peidong Su (Journal of Environmental Chemical Engineering, 2026)

Performance of Wetland in Pollutant Removal: a Review - Yifan Zhuo; Sangar Khan; Wenting Liu; Tingting Hu; Yuke Duan; Zongwei Lin; Xinxin Qi; Collins Oduro; Hongli Mu; Naicheng Wu (Water, Air, & Soil Pollution, 2026)

Early-life BPS exposure induces reproductive toxicity in offspring mice via ferroptosis - Yan Su; Xinxin Guo; Nuo Xu; Mengfen Pan; Kaixing Lin; Huaicai Zeng; Qingzhi He (Reproductive Toxicology, 2026)

Corrigendum to “In vitro/vivo evaluation of novel mitochondrial targeting charge-reversal polysaccharide-based antitumor nanoparticle” [Carbohydrate Polymers Volume 234 (2020) 115930] - Lei Fang; Hua Lin; Zhenfeng Wu; Zhen Wang; Xinxin Fan; Ziting Cheng; Xiaoya Hou; Daquan Chen (Carbohydrate Polymers, 2026)

Inhibition of miR ‐33 Alleviates Inflammation Response in Ctenopharyngodon idella Kidney Cells Induced by Chloroquine/Lipopolysaccharide - Lulu Yang; Mengjun Lin; Weifang Zhao; Yuru Zhang; Xinxin Xu; Xianglin Cao; Ronghua Lu (Journal of Fish Diseases, 2026)
A previous study in our laboratory revealed that microRNA‐33 (miR‐33) regulated autophagy initiation and inflammatory response by targeting Atg5 ; furthermore, in this study, chloroquine (CQ), lipopolysaccharide (LPS) and the miR‐33 inhibitor were transfected into Ctenopharyngodon idella kidney (CIK) cells to explore whether miR‐33 regulated late‐stage autophagy and inflammatory response induced by LPS. The results showed that CQ inhibited the fusion of autophagosome and lysosome and significantly increased the secretion of pro‐inflammatory cytokines ( p p beclin‐1 , atg5 , atg7 and atg12 did not recover after inhibiting miR‐33 ( p > 0.05). But the expression of tnf‐α , il‐6 , il‐1β , il‐8 and nf‐κb , as well as the secretion of TNF‐α, IL‐6, IL‐12 and IL‐1β, were significantly downregulated, and the activities of ALP, SOD and CAT were significantly increased ( p p tnf‐α , il‐6 , il‐1β , il‐8 and nf‐κb ; inhibiting the secretion of TNF‐α, IL‐6, IL‐12 and IL‐1β; and increasing the activities of ACP, ALP, SOD and CAT ( p

Human settlement doubled global oceanic island erosion and fire regimes during the early colonization stage - Fan Zhang; Huawei Wang; Chuan-Chou Shen; Jian Lin; Kai Zhou; Yongshun Chen; Kunshan Bao; Xinxin Li (Global and Planetary Change, 2026)

From brewing dynamics to population health: A Nationwide investigation of bisphenol analogues contamination and exposure risk in tea from China - Xinjie Li; Kai Lin; Zhihong Huang; Yiming Ge; Xinxin Tang; Bingjun Lu; Xulong Chen; Yiran Chen; Xiangxuan Kong; Yi Chen; Shaoyou Lu (Food Chemistry, 2026)

Molecular characterization of a novel partitivirus from quinoa (Chenopodium quinoa) in China - Wenqi Mao; Jiajia Lin; Zhongtian Xu; Penghuan Rui; Xinxin Fang; Hongying Zheng; Yuwen Lu; Jianping Chen; Fei Yan; Guanwei Wu (Archives of Virology, 2026)

Material, microbial and metabolism pathway perspectives on understanding the nitrogen/iron co-doped biochar enhanced methane production in brewery wastewater anaerobic digestion - Junguo He; Yili Wang; Yuanyi Zhao; Heliang Pang; Lin Li; Yunlong Liu; Xinxin Cui; Tong Wei; Suiyin Yu (Journal of Water Process Engineering, 2026)

Methanogenic efficiency of anaerobic digestion under sulfaquinoxaline sodium (SQ-Na) stress: Insights from enzyme, microbial community and metagenome analyses - Junguo He; Yuanyi Zhao; Heliang Pang; Yili Wang; Lin Li; Yunlong Liu; Xinxin Cui; Tong Wei; Shengye Duan; Suiyin Yu (Journal of Water Process Engineering, 2026)

Maillard-induced pea protein isolate/carboxymethyl chitosan conjugates: Synthesis, characterization, and applications in O/W emulsions - Wenhao Liu; Xiaoye Xu; Kehao Li; Siya Lin; Xinxin Zeng; Lihui Duan; Yan Huang; Shini Ma; Xiaoyan Liu; Yajie Shen; Jie Pang; Chunhua Wu (Food Research International, 2026)

Multidrug-resistant plasmid modulates ammonia oxidation efficiency in Nitrosomonas europaea through cyclic di-guanylate and acyl-homoserine lactones pathways - Jinrui Cao; Chen Zhao; Lin Bo; Xinxin He; Yuchao Liu; Shang Wang; Bin Xue; Jingfeng Wang (Bioresource Technology, 2026)

Deciphering Ferroptosis-Related Astrocyte Subpopulations and Diagnostic Biomarkers in Parkinson’s Disease through RNA Transcriptomics - Zhongying Gong; Dan Guo; Yufeng Lin; Zhiwei Liu; Mengdi Lv; Xinxin Liu; Mingshuo Sun; Linlin Wang; Tianman Zhao; Zhiyun Wang; Xue Xue (Molecular Neurobiology, 2026)

Aptamer conformation sensing in nanopore for on-site quantitative detection of cadmium ions at nanomolar concentrations - Shujun He; Ronghui Liu; Xinxin Bao; Jiayuan Pang; Xi Zhang; Yue Liu; Wenfu Lin; Jiadun Liu; Tianxin Li; Yao Li; Yi Li; Xinrong Guo (Analytica Chimica Acta, 2026)

One-pot fabrication of highly stable and luminescent InP quantum dots nanobeads through multifunctional polymer encapsulation for lateral flow immunoassay - Xinxin Chen; Qingbiao Zheng; Xiaoquan Li; Li Wang; Lifang Zhang; Yuxin Zhang; Lei Wang; Yanbing Lv; Lin Song Li; Ruili Wu (Analytica Chimica Acta, 2026)

Surface soil phytoliths of upland rice fields in southern China - Xinxin Zuo; Ying Zhou; Peng Xu; Guizhou Liu; Liting Chen; Yingjun Lin; Lin Ren; Hui Xie; Xiujia Huan (Plant and Soil, 2025)

Electrode interfacial wettability engineering for high-efficiency synthesis of dimethyl sebacate via Kolbe electrolysis - Linchuan Cong; Xinxin Li; Fuyu Han; Yupeng Wu; Kewen Ma; Ciduo Wang; Nan Lin; Haibo Lin (Chemical Engineering Journal, 2025)

Experimental study on the suppression effect of composite ultrafine dry powder fire extinguishing agents containing ternary layered double hydroxides on hydrogen deflagration - Min Hua; Yuhang Chen; Lin Zhu; Sijia Xue; Xinxin Guo; Xuhai Pan (Chemical Engineering Journal, 2025)

Flame-retardant ladder-like polysilsesquioxane composites enabled by dual crosslinking and functional nano-filler integration - Hui Liu; Xinxin Cai; Wen Li; Jiwen Hu; Yuewen Huang; Bin Wang; Shudong Lin (Chemical Engineering Journal, 2025)

Photoresponsive leaf-like structured two-dimensional metal-organic framework/nanocellulose crystal composites for efficient and rapid adsorption of pollutants from wastewater - Saisai Li; Luying Wang; Juan Dai; Na Zhang; Li Zhao; Shuyun Zheng; Xinxin Li; Caicai Lin; Dashuai Zhang; Qiang Li (Chemical Engineering Journal, 2025)

Gas-solid dual barrier strategy to efficiently enhance flame-retardancy and smoke-suppression of cellulose aerogel - Xiaolei Luo; Linyue He; Longfei Sun; Xinxin Chen; Lin Liu; Juming Yao; Yurong Cai (Carbohydrate Polymers, 2025)

Gipc3 Mutation Might Cause Sensorineural Hearing Loss by Inhibiting Mitophagy in Inner Ear Hair Cells - Xinxin Li; Jing Wang; Lin Shi; Liang Wang (Molecular Neurobiology, 2025)

Transferrin receptor 1 is an entry factor for Japanese encephalitis virus - Qing Yang; Shengda Xie; Yundi Zhao; Xinxin Lin; Ning Wei; Miaolei Shi; Ruibing Cao (Veterinary Microbiology, 2025)

Smartphone-assisted ultrasensitive colorimetric strategy based on Cu-CN single-atom nanozyme for acrylamide detection in fried food - Jia Ge; Xiaoyu Sun; Xinxin Li; Yu Yang; Lin Zhang; Lingbo Qu; Zhaohui Li (Food Chemistry, 2025)

A new quantitative characterization method of absolute methane adsorption isotherm in coal - Biao Hu; Zeyu Ren; Shugang Li; Xinxin He; Haifei Lin; Yang Bai; Dongjie Yan; Rongwei Luo (Chemical Engineering Journal, 2025)

Ion/electron/stress-triple-regulated Li deposition via multifunctional bismuth species in sulfide-based all-solid-state lithium metal batteries - Ziling Jiang; Siwu Li; Wenwen Hu; Shiyu Liu; Lin Li; Jie Yang; Miao Deng; Ziyu Lu; Xinxin Wang; Qin Chen; Hui Yang; Chen Liu; et al. (Chemical Engineering Journal, 2025)

AIM2-PANoptosome-driven PANoptosis in hepatic lipid dysregulation induced by β-HCH and nanoplastics co-exposure - Qizhuan Lin; Helei Cai; Fan Yu; Changyong Gong; Yize Wu; Qiufang Wu; Feiqin Xie; Wenhui Xu; Shihua Chen; Xinxin Yao; Libo Jin; Renyi Peng (Apoptosis, 2025)

Transcriptome analysis revealed that largemouth bass (Micropterus salmoides) may mobilize liver lipid metabolism to provide energy for adaptation to hypertonic stress - Xinxin Wang; Chaoyue Deng; Wenyan Lin; Huapeng Chen; Haoran Yu; Shukui Sun; Junlong Sun; Jian Luo; Feibiao Song (Aquaculture, 2025)

Effect of stormwater and land use on biogeochemical transformations of dissolved and particulate phosphorus in freshwater systems - Sangar Khan; Yuting Wang; Paul. J Milham; Zongwei Lin; Xinxin Qi; Huimin Gao; Yuke Duan; Jiuli Shi; Collins Oduro; Habib Ullah; Kamel M. Eltohamy; Naicheng Wu (Water Research, 2025)

An attractive vaccine candidate based on AP205 VLPs fusing with a receptor-binding domain of a newly emerged porcine deltacoronavirus strain in China - Xinyue Chang; Zhenyuan Zhang; Yilian Chen; Minghui Zhang; Fei Fei; Chenhao Ma; Zhiying Wang; Fazhi Xu; Lin Li; Xinxin Shan; Liang Li; Pei Sun; et al. (Veterinary Microbiology, 2025)

Constraining anthropogenic CO2 emissions using dense observations from OCO-3: Disentangling observed imprints over Xiamen-Zhangzhou-Quanzhou metropolitan area and challenges - Xinxin Ye; Weijiao Li; Thomas Lauvaux; Shuifa Lin; Ziwei Zhang; Yunxiao Lin; Jingfen Hua; Qin You; Jianyi Lin (Urban Climate, 2025)

The regulatory role of DELLA protein DkGAI1 in persimmon dwarfism - Xialin Ye; Xinyi Yu; Hongcheng Liu; Xinxin Lin; Xuting Wu; Jiangtao Yu; Shenchun Qu (Plant Science, 2025)

Impact of small hydropower plants on microbial community structure and functions in benthic biofilms - Huimin Gao; Xinxin Qi; Zongwei Lin; Mali Li; Guohao Liu; Yuanyuan Lv; Sangar Khan; Naicheng Wu (Journal of Environmental Management, 2025)

Multi-omics analysis reveals BPF exposure causes hepatic glucose and lipid metabolism disorder in rats by disrupting energy homeostasis - Zhi Li; Yuanyuan Wu; Mingqing Qian; Bingya Zhang; Xinxin Deng; Penghui Mao; Zhonghua Fan; Xu Fang; Lin Cheng; Xuan Liu; Li Wang; Hui Liu (Toxicology, 2025)

Red mud-based magnetic biochar composite as a peroxydisulfate activator for tetracycline degradation - Chao Shen; Xinxin Dong; Jing Yang; Yafei Li; Shihai Cui; Dapeng Zhang; Xiaochen Lin (Environmental Research, 2025)

Comparing multiple assessment methods based on water quality, habitat and organism indicators: unveiling the ecological health of Ningbo’s urban rivers - Jiuli Shi; Juanjuan Chen; Yifan Yang; Guohao Liu; Jiaze Liu; Zhenhui Zhou; Zongwei Lin; Xinxin Qi; Kan Wang; Naicheng Wu (Environmental Monitoring and Assessment, 2025)

Joint technique “parallel peptide synthesis & de novo sequencing” development for the structure verification and high-throughput activity screening of biological peptides from sea cucumber (Stichopus japonicus) intestinal hydrolysate - Yimeng Li; Shengfang Gao; Xiaohui Zhang; Zhuo Cao; Youyou Guo; Runkun Zhao; Yonggang Liu; Xinxin Li; Hongying Lin; Qi Qin; Bingqing Yi; Guodong Zhao (Food Research International, 2025)

A redox-modulating coating with multi-enzyme activity on engineered nanoparticles: An effective strategy for enhancing the control of plant bacterial diseases - Zhenghao Ding; Liwei Liu; Qingqing Song; Lin Chen; Guangdi Wang; Hong Li; Xinxin Tuo; Zhibing Wu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2025)

Formation of aroma characteristics driven by microorganisms during long-term storage of Liubao tea - Chang Xu; Jinming Zhang; Yani Pan; Xinyu Feng; Anran Yan; Xinxin Wang; Lin Xiang; Haowei Guo; Lixin He; Tianyuan Chen; Fangyuan Fan; Shuying Gong; et al. (Food Chemistry, 2025)

Enhancing anaerobic digestion of sludge with dual-heteroatom-doped biochar derived from digested sludge: In-situ reuse of anaerobic residues for system self-circulation - Shengye Duan; Junguo He; Yijie Zhong; Lin Li; Xiang Zou; Qiupeng Cai; Ruimiao Zhang; Xinxin Cui; Yuanyi Zhao; Yunlong Liu; Jie Zhang (Environmental Research, 2025)

MiR ‐33‐Mediated Regulation of Autophagy and Inflammation in CIK Cells Through Atg5 - Lulu Yang; Mengjun Lin; Weifang Zhao; Yuru Zhang; Xinxin Xu; Xianglin Cao; Guoxing Nie; Ronghua Lu (Journal of Fish Diseases, 2025)
MicroRNA‐33 (miR‐33) plays a critical role in the regulation of autophagy and inflammatory responses. In this study, C. idella kidney (CIK) cells were transfected with a miR‐33 mimic or inhibitor and Atg5 was overexpressed or silenced to elucidate the regulatory mechanism of miR‐33. Our findings revealed that the miR‐33 mimic significantly decreased the expression of LC3B (a marker of autophagy activation), and the level of autophagy‐related genes ( Beclin‐1 , Atg5 and LC3‐1 ) was also significantly downregulated ( p p Beclin‐1 and Atg5 ( p p Atg5 as a direct target gene of miR‐33. Overexpression of Atg5 significantly upregulated the levels of Beclin‐1 , Atg5 , Atg4C and LC3‐1 , along with a reduction in the secretion of proinflammatory factors (TNF‐α, IL‐12 and IL‐1β). Besides, the activities of superoxide dismutase (SOD) and catalase (CAT) were significantly increased ( p Atg5 expression caused significant downregulation in the expression levels of Beclin‐1 , Atg5 , Atg12 , Atg4C and LC3‐1 , resulting in increased secretion of TNF‐α, IL‐12 and IL‐1β and decreased activity of acid phosphatase (ACP) and SOD ( p Atg5 . This study not only enhances the understanding of the mechanism by which miR‐33 regulates autophagy and inflammation in fish but also provides a theoretical foundation and novel insights to improve disease management in the fish aquaculture industry.

JEV NS1' protein enhances cell-to-cell viral spread by inducing the formation of tunneling nanotubes - Ziyu Cao; Shengda Xie; Xingmiao Yang; Ning Wei; Yundi Zhao; Mengyuan Sun; Xinxin Lin; Miaolei Shi; Ruibing Cao (Veterinary Microbiology, 2025)

Formaldehyde oxidation reaction enhanced by interface engineering of Cu/Cu2O/Co(OH)2 composite electrocatalyst for bipolar hydrogen production - Zi Qiang Ma; Chang Bao Han; Wen Kang Zhao; De Cai Fang; Yi Lin Zhao; Chang Xin Liu; Xinxin Wang; Ling Sun; Xue Mei Song (Chemical Engineering Journal, 2025)

Experimental Study of the Hydrodynamic Forces of Pontoon Raft Aquaculture Facilities Around a Wind Farm Monopile Under Wave Conditions - Deming Chen; Mingchen Lin; Jinxin Zhou; Yanli Tang; Fenfang Zhao; Xinxin Wang; Mengjie Yu; Qiao Li; Daisuke Kitazawa (Journal of Marine Science and Engineering, 2025)
The integrated development of offshore wind power and marine aquaculture represents a promising approach to the sustainable utilization of ocean resources. The present study investigated the hydrodynamic response of an innovative combination of a wind farm monopile and pontoon raft aquaculture facilities (PRAFs). Physical water tank experiments were conducted on PRAFs deployed around a wind farm monopile using the following configurations: single- and three-row arrangements of PRAFs with and without a monopile. The interaction between the aquaculture structure and the wind farm monopile was examined, with a particular focus on the mooring line tensions and bridle line tensions under different wave conditions. Utilizing the wind farm monopile foundation as an anchor, the mooring line tension was reduced significantly by 16–66% in the single-row PRAF. The multi-row PRAF arrangement experienced lower mooring line tension in comparison with the single-row PRAF arrangement, with the highest reduction of 73%. However, for the bridle line tension, the upstream component was enhanced, while the downstream one was weakened with a monopile, and they both decreased in the multi-row arrangement. Finally, we developed numerical models based on flume tank tests that examined the interactions between the monopile and PRAFs, including configurations of a single monopile, along with single- and three-row arrangements of PRAFs. The numerical simulation results confirmed that the monopile had a dampening effect on the wave propagation of 5% to 20%, and the impact of the pontoons on the monopile was negligible, implying that the integration of aquaculture facilities around wind farm infrastructure may not significantly alter the hydrodynamic loads experienced by the monopile.

Histological and transcriptome analysis of gonadal development provides new insights into the characteristics of sex differentiation and the screening of key genes in the golden pompano (Trachinotus blochii) - Feibiao Song; Huan Liang; Zhi Li; Da Zheng; Huapeng Chen; Xinxin Wang; Chaoyue Deng; Wenyan Lin; Changlin Chen; Junlong Sun; Li Zhou; Jian Luo (Aquaculture, 2025)

Interaction of microalgae, nitrogen and arsenic in a water environment co-polluted by nitrogen and arsenic: current knowledge and future perspectives - Youwen Li; Xinxin Zhao; Zhaoqi Zhong; Fanfan Ju; Hui Liu; Ning Lin; Xianghao Zha (Aquatic Ecology, 2025)

Blood cadmium levels of children aged 0–6 years in China: A national cross-sectional study - Xinxin Zhang; Yin Lin; Yuqing Wang; Junxia Liu; Xinyi Cui; Yong Chen; Yan Wu; Fengxiu Ouyang; Xianting Jiao; Kang Cai; Chonghuai Yan (Science of The Total Environment, 2025)

Recent advancements in antibiotics removal by bio-electrochemical systems (BESs): From mechanisms to application of emerging combined systems - Jing Tang; Zijun Li; Xinxin Xiao; Baicheng Liu; Wei Huang; Qingqing Xie; Chenrui Lan; Shuai Luo; Lin Tang (Water Research, 2025)

Patterns and drivers of terrace abandonment in China: Monitoring based on multi-source remote sensing data - Dan Lu; Kangchuan Su; Zhanpeng Wang; Mengjie Hou; Xinxin Li; Aiwen Lin; Qingyuan Yang (Land Use Policy, 2025)

Anaerobic digestion and biochar/hydrochar enhancement of antibiotic-containing wastewater: Current situation, mechanism and future prospects - Yuanyi Zhao; Junguo He; Heliang Pang; Lin Li; Xinxin Cui; Yunlong Liu; Weixun Jiang; Xinping Liu (Environmental Research, 2025)

In-situ online investigation of biogenic volatile organic compounds emissions from tropical rainforests in Hainan, China - Xi Chen; Daocheng Gong; Shiwei Liu; Xinxin Meng; Zhu Li; Youjing Lin; Qinqin Li; Ruiyun Xu; Sijun Chen; Qinghua Chang; Fangyuan Ma; Xiaoxiao Ding; et al. (Science of The Total Environment, 2024)

Ru induced charge redistribution of MnO2 spheric nanozyme boosted hydrogen sulfide selective detection and cystathionine γ-lyase activity sensitive evaluation - Zhao Li; Xuan Zhang; Haorong Cheng; Zhongyuan Gu; Changchun He; Ju Wang; Xinxin Shi; Weidan Na; Tongxiang Li; Lin Tian (Chemical Engineering Journal, 2024)

Decomposing high uncertainty in greenhouse gas mitigation pathways in emerging regions: An approach to evaluate risks toward carbon neutrality - Hui Han; Xinxin Ye; Yahui Bian; Shuifa Lin; Yu-Sheng Shen; Zhi Huang; Jianyi Lin (Science of The Total Environment, 2024)

Differential impacts of small hydropower plants on macroinvertebrate communities upstream and downstream under ecological flow - Zongwei Lin; Xinxin Qi; Mali Li; Yuke Duan; Huimin Gao; Guohao Liu; Sangar Khan; Hongli Mu; Qinghua Cai; Beata Messyasz; Naicheng Wu (Journal of Environmental Management, 2024)

Small hydropower plants affect aquatic community diversity: A longitudinal study under ecological flow - Xinxin Qi; Zongwei Lin; Huimin Gao; Mali Li; Yuke Duan; Guohao Liu; Sangar Khan; Hongli Mu; Beata Messyasz; Naicheng Wu (Journal of Environmental Management, 2024)

Self-template synthesis of PBA/MOF hollow nanocubes for aqueous battery - Yecan Pi; Hao Lin; Zhenyang Meng; Ziming Qiu; Yichun Su; Xinxin Hang; Huan Pang (Chemical Engineering Journal, 2024)

Sustainable bioleaching of heavy metals from coal tailings using Bacillus inaquosorum B.4: Mechanistic insights and environmental implications - Qingshan Zhang; Lin Ma; Yaoli Peng; Xinxin Yan (Journal of Environmental Chemical Engineering, 2024)

Cellulose nanofiber powered interface engineering strategy to manufacture mechanically stable, moldable, recyclable, and biodegradable cellulose foam - Longfei Sun; Jing Lu; Xinxin Chen; Hanfei Zhao; Lin Liu; Juming Yao (Chemical Engineering Journal, 2024)

Flexible sensor based on conformable, sticky, transparent elastomers for electronic skin - Xinxin Cai; Xinqi Wang; Fuping Bian; Jiayi Li; Ruixiang Zhou; Jiwen Hu; Shudong Lin (Chemical Engineering Journal, 2024)

Identification of Floating Green Tide in High-Turbidity Water from Sentinel-2 MSI Images Employing NDVI and CIE Hue Angle Thresholds - Lin Wang; Qinghui Meng; Xiang Wang; Yanlong Chen; Xinxin Wang; Jie Han; Bingqiang Wang (Journal of Marine Science and Engineering, 2024)
Remote sensing technology is widely used to obtain information on floating green tides, and thresholding methods based on indices such as the normalized difference vegetation index (NDVI) and the floating algae index (FAI) play an important role in such studies. However, as the methods are influenced by many factors, the threshold values vary greatly; in particular, the error of data extraction clearly increases in situations of high-turbidity water (HTW) (NDVI > 0). In this study, high spatial resolution, multispectral images from the Sentinel-2 MSI mission were used as the data source. It was found that the International Commission on Illumination (CIE) hue angle calculated using remotely sensed equivalent multispectral reflectance data and the RGB method is extremely effective in distinguishing floating green tides from areas of HTW. Statistical analysis of Sentinel-2 MSI images showed that the threshold value of the hue angle that can effectively eliminate the effect of HTW is 218.94°. A test demonstration of the method for identifying the floating green tide in HTW in a Sentinel-2 MSI image was carried out using the identified threshold values of NDVI > 0 and CIE hue angle 0), resulting in better consistency of the identification of the floating green tide and its distribution in the true color image. The method enables rapid and accurate extraction of information on floating green tide in HTW, and offers a new solution for the monitoring and tracking of green tides in coastal areas.

Hepatitis B virus core protein as a Rab-GAP suppressor driving liver disease progression - Yu Su; Fan Bu; Yuanfei Zhu; Le Yang; Qiong Wu; Yuan Zheng; Jianjin Zhao; Lin Yu; Nan Jiang; Yongxiang Wang; Jian Wu; Youhua Xie; et al. (Science Bulletin, 2024)

Preharvest GA3 treatment at optimized time points enhanced the storability of ‘Shixia’ longan fruit - Tao Luo; Libing Long; Tingting Lai; Xiaolan Lin; Chenning Ning; Ziying Lai; Xinxin Du; Liang Shuai; Dongmei Han; Zhenxian Wu (Postharvest Biology and Technology, 2024)

Emerging conductive ceramic membranes for water purification and membrane fouling mitigation - Zhiwei Lin; Lie Liu; Chunhui Zhang; Peidong Su; Xinxin Zhang; Xuezhi Li; Yanan Jiao (Chemical Engineering Journal, 2024)

Injectable photocrosslinkable acellular cartilage matrix hydrogel loaded with exosomes for promoting growth plate injury repair - Xinxin Si; Quan Zhang; Bo Ning; Lei Qiang; Qiang Li; Yihao Liu; Minjie Fan; Jing Shan; Guanlu Shen; Zichen Lin; Pengfei Zheng (Chemical Engineering Journal, 2024)

Innovative insights into organic nitrogen degradation through protein family domains analysis in chicken and pig manure composting using metagenomic sequencing - Lin Zhu; Caihong Huang; Lipin Li; Simiao Wang; Xinxin Wu; Guangchun Shan; Yu Tian (Bioresource Technology, 2024)

Stefin B alleviates the gouty arthritis in mice by inducing the M2 polarization of macrophages - Shishui Lin; Xu Hu; Yang Li; Jiyue Huang; Rui Zhang; Xinxin Bai; Shaohuang Weng; Min Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
The present study aims to explore the therapeutic effect of Stefin B on gouty arthritis (GA) and the polarization of macrophages in mice. Stefin B-overexpressed or knockdown M0 macrophages were constructed. The GA model was established in mice by injecting 25 mg/mL MSU, followed by a single injecting of Stefin B-overexpressing adenovirus vector (GA model + Stefin B OE) or an empty vector (GA model + Stefin B OE NC). Stefin B was found lowly expressed in M1 macrophages. CD206 was markedly upregulated and IL-10 release was signally increased in Stefin B-overexpressed macrophages. In gouty arthritis mice, marked redness and swelling were observed in the ankle joint. Dramatical infiltration of inflammatory cells was observed in the GA model and GA model + Stefin B OE NC groups, which was suppressed in the Stefin B OE group. Increased proportion of F4/80 + CD86 + cells observed in GA mice was markedly repressed by Stefin B overexpression, accompanied by the declined level of Caspase-1 and IL-17. Collectively, Stefin B alleviated the GA in mice by inducing the M2 polarization of macrophages.

Retrieval and spatiotemporal variation of total suspended matter concentration using a MODIS-derived hue angle in the coastal waters of Qinhuangdao, China - Lin Wang; Xiang Wang; Qinghui Meng; Yanlong Chen; Xinxin Wang; Lingling Jiang; Yuhao Shang (Frontiers in Marine Science, 2024)
The CIE hue angle has significant potential in marine ecology and environment monitoring using remote sensing methods. It is calculated from the remote sensing reflectance ( R rs ) of all visible bands, which serves as a comprehensive indicator of seawater radiance information and represents one of the key quantitative parameters for assessing seawater color. In this study, a remote sensing retrieval model of total suspended matter concentration (TSM) was developed using the in situ measured data acquired in the coastal waters of Qinhuangdao from 2013 to 2021. This model, based on the CIE hue angle, achieved performance metrics of R 2 = 0.68, MAPE=24.47%, and RMSE=2.72 mg/L, demonstrating better accuracy than traditional empirical models that utilize fewer bands. Based on this model, the monthly and interannual TSM in the coastal waters of Qinhuangdao from 2003 to 2023 were retrieved. Influenced by natural factors, such as the monsoons, the TSM in the coastal waters of Qinhuangdao generally exhibited a trend of first decreasing and then increasing from January to December. Except for certain anomalous years (2007, 2008, 2017, etc.), the overall variation process of TSM from 2003 to 2023 showed an initial increase followed by a decrease, closely related to the pollution reduction management requirements implemented by the Chinese government in different periods. The findings of this paper demonstrate that the coastal waters of Qinhuangdao have become clearer, and the ecological environment has been effectively improved as a result of the Chinese government’s vigorous promotion of ecological civilization construction, adhering to the development concept that ‘lucid waters and lush mountains are invaluable assets’, and by introducing the action plan for the comprehensive treatment of pollution in the Bohai Sea.

Preparation of a long-term mildew resistant and strong soy protein adhesive via constructing multiple crosslinking networks - Yanqiu Chen; Xinxin Huang; Guang Wang; Hanbing Liu; Xixiang Lin; Pingan Song; Wenrui Zhou; Jianlin Luo; Qiang Gao (Chemical Engineering Journal, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Construction, characterization, antioxidant activity and effects on properties in vitro digestion of selenium nanoparticles decorated with Cyperus esculentus polysaccharides - Chuang Zhai; Yicun Lin; Chunling Mao; Xinxin Li; Ran Zhang; Jiaming Liu; Ling Zhang (Food Bioscience, 2024)

Characterization of a novel recombinant NADC30‑like porcine reproductive and respiratory syndrome virus in Shanxi Province, China - Jianle Ren; Shanshan Tan; Xinxin Chen; Xizhen Wang; Yiting Lin; Yi Jin; Sheng Niu; Ying Wang; Xiaolong Gao; Libin Liang; Junping Li; Yujun Zhao; et al. (Veterinary Research Communications, 2024)

Candidate gene mining of GA-mediated regulation of pear fruit shape - Zeyu Xue; Ru Yang; Yadong Wang; Yuchen Ma; Yujing Lin; Zhengao Li; Yuqin Song; Xinxin Feng; Liulin Li (Horticulture, Environment, and Biotechnology, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

The Mh-miR393a-TIR1 module regulates Alternaria alternata resistance of Malus hupehensis mainly by modulating the auxin signaling - Xinyi Yu; Kaixu Hu; Xiaoyue Geng; Lifang Cao; Tingting Zhou; Xinxin Lin; Hongcheng Liu; Jingrui Chen; Changguo Luo; Shenchun Qu (Plant Science, 2024)

Occurrence and health risk of pesticide residues in Chinese herbal medicines from Shandong Province, China - Fangfang Chen; Tianliang Zhang; Peirui Xiao; Lijun Shao; Xinxin Zhang; Lin Wang; Xiaofei Ren; Chuan Qin; Yanni Jiao (Environmental Science and Pollution Research, 2024)

PM2.5 air quality and health gains in the quest for carbon peaking: A case study of Fujian Province, China - Yahui Bian; Xiaobo Huang; Shuifa Lin; Hui Han; Jinsheng Chen; Jianyi Lin; Xinxin Ye (Science of The Total Environment, 2024)

Dynamics of microbial functional guilds involved in the humification process during aerobic composting of chicken manure on an industrial scale - Jie Yang; Zhe Du; Caihong Huang; Wei Li; Beidou Xi; Lin Zhu; Xinxin Wu (Environmental Science and Pollution Research, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Multidrug-resistant plasmid RP4 inhibits the nitrogen removal capacity of ammonia-oxidizing archaea, ammonia-oxidizing bacteria, and comammox in activated sludge - Zhaohui Zhang; Lin Bo; Shang Wang; Chenyu Li; Xi Zhang; Bin Xue; Xiaobo Yang; Xinxin He; Zhiqiang Shen; Zhigang Qiu; Chen Zhao; Jingfeng Wang (Environmental Research, 2024)

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Late Neolithic to Bronze Age water management and upland rice cultivation in the mountainous areas of Southeastern China Coast - Guiping Wu; Xinxin Zuo; Wei Wu; Lin Ren; Chunming Wu; Yingjun Lin; Hui Xie; Yaoyao Pei; Guiyu Zhou (Quaternary International, 2024)

Understanding the impact of cultivated land-use changes on China's grain production potential and policy implications: A perspective of non-agriculturalization, non-grainization, and marginalization - Dan Lu; Zhanpeng Wang; Kangchuan Su; Yajuan Zhou; Xinxin Li; Aiwen Lin (Journal of Cleaner Production, 2024)

Boosting decarboxylation of monomethyl adipate coupling to dimethyl sebacate through Pt electrode at high current density - Linchuan Cong; Yupeng Wu; Nan Lin; Xinxin Li; Fangbing Liu; Fuyu Han; Jin Yang; Ciduo Wang; Haibo Lin (Chemical Engineering Journal, 2024)

A polylactide based multifunctional hydrophobic film for tracking evaluation and maintaining beef freshness by an electrospinning technique - Xinxin Liu; Xiushuang Song; Dejiao Gou; Hongli Li; Lin Jiang; Minglong Yuan; Mingwei Yuan (Food Chemistry, 2023)

Pathological observation and transcriptomic analysis of thymus injury in PRRSV-infected piglets - Naying Su; Zhengdan Lin; Xi Liu; Xiuxiu Sun; Xinxin Jin; Helong Feng; Cunlin Zhan; Xueying Hu; Changqin Gu; Wanpo Zhang; Guofu Cheng (Veterinary Research Communications, 2023)
The thymus, the central immune organ in mammals, plays an important role in immune defense. Porcine reproductive and respiratory syndrome virus (PRRSV) infection in piglets can cause thymus injury and immunosuppression. However, the mechanisms of thymus injury remain unknown. This study was aimed at investigating the specific manifestations of thymus injury through the construction of a PRRSV-infected piglet model and histopathological observation. In this study, fourteen 40-day-old PRRSV-free piglets were randomly divided into two groups, eleven of which were intramuscularly injected with 3 mL of PRRSV WUH3 virus suspension (10 6 PFU /mL) in the infection group, and three of which were sham-inoculated with 3 mL of RPMI-1640 medium in the control group. Clinical necropsy and samples collection were performed on day 8 after artificial infection. With the Illumina platform, the transcriptomes of piglet thymus tissues from infected and control piglets were sequenced to explore the relationships of differentially expressed genes (DEGs) and signaling pathways with thymus injury. The immune organs of PRRSV-infected piglets were severely damaged. The histopathological findings in the thymus indicated that PRRSV infection was associated with a large decrease in lymphocytes, cell necrosis and cell apoptosis; an increase in blood vessels and macrophages; thymic corpuscle hyperplasia; and interstitial widening of the thymic lobules. The transcriptomic analysis results revealed that the Gene Ontology functions of DEGs were enriched primarily in biological processes such as angiogenesis, regulation of angiogenesis and positive regulation of cell migration. Moreover, greater numbers of blood vessels and macrophages were observed in the thymus in PRRSV-infected than control piglets. KEGG pathway enrichment analysis revealed that the DEGs were significantly enriched in the Toll-like receptor signaling pathway, chemokine signaling pathway, IL-17 signaling pathway and TNF signaling pathway. The expression of TLR8, IRF5, the chemokines CCL2, CCL3L1 and CCL5; and their receptors CCR1, CCR2 and CCR5 was significantly up-regulated in PRRSV infection, thus suggesting that these cytokines were associated with the pathological processes of thymus injury.

Multifunctional regulation of NADPH oxidase in growth, microsclerotia formation and virulence in Metarhizium rileyi - Liqin Fan; Bingjie Li; Jiahui Wang; Xinxin Li; Feilong Ma; Fang Du; Hongli Li; Yunlong Lin (Biotechnology Letters, 2023)

Pectin-nanolignin composite films with water resistance, UV resistance, and antibacterial activity - Shikai Zhang; Xinxin Cheng; Quanbin Fu; Yijing Li; Peng Wu; Yiheng Qiao; Jianfeng Yan; Lin Si; Geoffrey I.N. Waterhouse; Houshen Li; Shiyun Ai (Food Hydrocolloids, 2023)

A review of advances in mechanical behaviors of the underground energy transmission pipeline network under loads - Qiang Zheng; Qian Xu; Zekai Shu; Di Yang; Weiwang Chen; Nevzat Akkurt; Hui Zhang; Lin Lin; Xinxin Zhang; Yulong Ding (Gas Science and Engineering, 2023)

A strong soy protein-based adhesive with excellent water retention - Xinxin Huang; Yanqiu Chen; Xixiang Lin; Jianzhang Li; Qiang Gao (Chemical Engineering Journal, 2023)

Characteristics of digested sludge-derived biochar for promoting methane production during anaerobic digestion of waste activated sludge - Shengye Duan; Junguo He; Xiaodong Xin; Lin Li; Xiang Zou; Yijie Zhong; Jie Zhang; Xinxin Cui (Bioresource Technology, 2023)

Condensation retardation performance of metal-organic framework-based composite humidity-control materials in a radiation cooling room - Huibo Zhang; Lin Fu; Xinxin Wang; Jiang Chang (Building and Environment, 2023)

Multidrug-resistant plasmid RP4 increases NO and N2O yields via the electron transport system in Nitrosomonas europaea ammonia oxidation - Jia Li; Chen Zhao; Chenyu Li; Bin Xue; Shang Wang; Xi Zhang; Xiaobo Yang; Zhiqiang Shen; Lin Bo; Xinxin He; Zhigang Qiu; Jingfeng Wang (Water Research, 2023)

Strategies for controlling gas evolution reactions to boost the divergent paired electrochemical upgrading of furfural in acidic environment - Xinxin Li; Linchuan Cong; Yupeng Wu; Nan Lin; Fangbing Liu; Deyuan Xin; Fuyu Han; Jin Yang; Weitong Chen; Haibo Lin (Chemical Engineering Journal, 2023)

A semitransparent and tough wood-based adhesive gels with excellent adhesion both in air and underwater for emergency pipeline repair - Minmin Chang; Jianlin Wang; Xinxin Liu; Qixuan Lin; Xiaohui Wang; Feng Peng; Junli Ren (Chemical Engineering Journal, 2023)

Innate and adaptive immune abnormalities underlying autoimmune diseases: the genetic connections - Xinxin Chi; Miaozhen Huang; Hailin Tu; Bin Zhang; Xin Lin; Huji Xu; Chen Dong; Xiaoyu Hu (Science China Life Sciences, 2023)

Developing a novel framework to re-examine half a century of compound drought and heatwave events in mainland China - Lin Zhao; Xinxin Li; Zhijiang Zhang; Moxi Yuan; Shao Sun; Sai Qu; Mengjie Hou; Dan Lu; Yajuan Zhou; Aiwen Lin (Science of The Total Environment, 2023)

Design and fabrication of anthocyanin functionalized layered clay/poly(vinyl alcohol) coatings on poly(lactic acid) film for active food packaging - Long Mao; Chengyu Wang; Jin Yao; Yating Lin; Xinxin Liao; Jing Lu (Food Packaging and Shelf Life, 2023)

Hyperoside attenuates Cd-induced kidney injury via inhibiting NLRP3 inflammasome activation and ROS/MAPK/NF-κB signaling pathway in vivo and in vitro - Ziyin Li; Weizuo Liao; Xinxin Yin; Lili Liu; Zhiqiang Zhao; Xiaodan Lu; Feifei Xu; Xiuqin Lin; Yingsi Chen; Jia Song; Zhini He; Qinzhi Wei; et al. (Food and Chemical Toxicology, 2023)

SATB1/SLC7A11/HO-1 Axis Ameliorates Ferroptosis in Neuron Cells After Ischemic Stroke by Danhong Injection - Sikai Zhan; Jiayin Liang; Huiting Lin; Jiale Cai; Xinxin Yang; Hongwei Wu; Junying Wei; Shumei Wang; Minghua Xian (Molecular Neurobiology, 2023)

Microfossil evidence of rice cultivation on the Southeast China Coast 7500 years ago - Xinxin Zuo; Jinqi Dai; Wei Wu; Jianhui Jin; Wei Ge; Yinping Wang; Lin Ren; Yingjun Lin; Yaoyao Pei; Hui Xie (Science China Earth Sciences, 2022)

Measuring the phase response of a seismometer using superimposed sine signals - Zhan Lin; Yuntian Teng; Bing Xue; Xinxin Ma (Journal of Seismology, 2022)

High-Throughput Identification of Antihypertensive Peptides (AHTPs) and Characterization of AHTP-Derived Genes in the Lined Seahorse (Hippocampus erectus) - Yu Huang; Xiyang Chen; Haoyue Shu; Panpan Xiao; Xueqiang Lin; Junmin Xu; Chao Bian; Xinxin You; Jian Yang; Qiong Shi (Frontiers in Marine Science, 2022)
Recently, the prevalence of hypertension has become a global challenge. Therefore, tremendous efforts have been made to identify and purify antihypertensive peptides (AHTPs) from food-derived proteins to aid the discovery of new hypotensive drugs with fewer side effects. In this study, we performed high-throughput prediction of AHTPs based on multi-omics data, providing an overview of AHTPs in the lined seahorse proteins and suggesting their potential application as bioactive agents to lower blood pressure. We identified 14,695 AHTP-derived genes in the lined seahorse, and most of them were supported by transcriptomic evidence, whereas only 495 genes were further detected by proteome sequencing. Among these predicted AHTP-derived genes, the longest titin had the most hits with 104 AHTPs, some of which were clustered in exon 158, 194, and 204. Another AHTP-rich group was in the collagen family, and four AHTP-rich collagens exhibited much higher transcription in the pouch than in other examined tissues, including brain, testis, and embryos. Additionally, antihypertensive triplets, comprised of the permutations of Gly, Pro, and Lys, prevailed in all collagen sequences due to the representative XaaYaaGly repeat units. In summary, our present findings provide a solid basis for understanding the abundance of various AHTPs in the lined seahorse as well as shed light on the development of antihypertensive products and drugs using seahorses as an important resource.

Comparison of the Curative Effects of Hip Arthroplasty with Bio-Type Femoral Stem and Cemented Femoral Stem in Elderly Patients with Unstable Osteoporotic Intertrochanteric Femur Fractures - Xinxin Lin; Keqin Yang; Haitao Tan; Fengping Gan; Jianzhong Jiang (Journal of Medical and Biological Engineering, 2021)

Lung injury induced by pyrrolizidine alkaloids depends on metabolism by hepatic cytochrome P450s and blood transport of reactive metabolites - Yisheng He; Wei Lian; Liang Ding; Xiaoyu Fan; Jiang Ma; Qing-Yu Zhang; Xinxin Ding; Ge Lin (Archives of Toxicology, 2021)

Isolation and identification of the Raoultella ornithinolytica-ZK4 degrading pyrethroid pesticides within soil sediment from an abandoned pesticide plant - Xiaoqing Zhang; Xiangxiang Hao; Shanshan Huo; Wanzhong Lin; Xinxin Xia; Kuai Liu; Bihua Duan (Archives of Microbiology, 2019)

Sigma-1 receptor protects against endoplasmic reticulum stress-mediated apoptosis in mice with cerebral ischemia/reperfusion injury - Xuemei Zhao; Lin Zhu; Danyang Liu; Tianyan Chi; Xuefei Ji; Peng Liu; Xuexue Yang; Xinxin Tian; Libo Zou (Apoptosis, 2019)

Screening and Genome Sequencing of Deltamethrin-Degrading Bacterium ZJ6 - Xiangxiang Hao; Xiaoqing Zhang; Bihua Duan; Shanshan Huo; Wanzhong Lin; Xinxin Xia; Kuai Liu (Current Microbiology, 2018)

A genome-wide association study on growth traits in orange-spotted grouper (Epinephelus coioides) with RAD-seq genotyping - Hui Yu; Xinxin You; Jia Li; Xinhui Zhang; Shuai Zhang; Shoujia Jiang; Xueqiang Lin; Hao-Ran Lin; Zining Meng; Qiong Shi (Science China Life Sciences, 2018)

Eburicoic acid from Laetiporus sulphureus (Bull.:Fr.) Murrill attenuates inflammatory responses through inhibiting LPS-induced activation of PI3K/Akt/mTOR/NF-κB pathways in RAW264.7 cells - Junzhi Wang; Pan Zhang; Haibo He; Xinxin Se; Wenjun Sun; Beiyan Chen; Lin Zhang; Ximing Yan; Kun Zou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Arabidopsis ANAC069 binds to C[A/G]CG[T/G] sequences to negatively regulate salt and osmotic stress tolerance - Lin He; Xinxin Shi; Yanmin Wang; Yong Guo; Kejun Yang; Yucheng Wang (Plant Molecular Biology, 2017)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

A Prospective Evaluation of the Combined Helical Tomotherapy and Chemotherapy in Pediatric Patients with Unresectable Rhabdomyosarcoma of the Temporal Bone - Xinxin Zhang; Kun Ma; Jaling Wang; Wenming Wu; Lin Ma; Deliang Huang (Cell Biochemistry and Biophysics, 2014)

Degradation of Acid Orange 7 in aqueous solution by dioxygen activation in a pyrite/H2O/O2 system - Feifei Hao; Weilin Guo; Xin Lin; Yanqiu Leng; Anqi Wang; Xinxin Yue; Liangguo Yan (Environmental Science and Pollution Research, 2014)

Analysis of synonymous codon usage patterns in the genus Rhizobium - Xinxin Wang; Liang Wu; Ping Zhou; Shengfeng Zhu; Wei An; Yu Chen; Lin Zhao (World Journal of Microbiology and Biotechnology, 2013)